The vertical transmission of time use choices - Benjamin Volland (Max Planck Institute of Economics, 2012)
The present paper analyzes intergenerational correlations in leisure time use between parents and their adult children in order to gain an understanding of the importance of genetics and early childhood learning mechanisms in preference formation. Data from the British Household Panel Survey (BHPS) is used to regress time use choices of children on the behavior of their parents after the former have left to form their own household. A principal component analysis on eight time use items reveals two identifiable components, associated with personal leisure time use outside the home, and voluntary work. Estimations find substantial and significant correlations for both components, but suggest that the variance in filial behavior explained by the variance in parental behavior is limited, ranging from 17% to 32% for personal leisure time use, and from 2% to 7% for voluntary work. Moreover we provide evidence that direct transmission of parental preferences to their children accounts for roughly 20% of the observable similarity between the two generations. These results are robust to a wide array of robustness checks, including changes in estimation technique, model specification, and data restrictions, and suggest that these correlations can be ascribed to preference transmission from parental to filial generation rather than to coordination between generations. Aside from adding to the growing economic literature on preference transmission models, it also provides empirical support for the strong impact of non-parental sources of preferences formation, voiced particularly in models of dual inheritance.
Keywords: J13; J22; 330; intergenerational transmission of preferences; preference dynamics; time use; relative importance; Zeitverwendung; Generationenbeziehungen; Präferenztheorie; Schätzung; Großbritannien